Plasmodium falciparum alters the trophoblastic barrier and stroma villi organization of human placental villi explants (2024)
Background: The sequestration of Plasmodium falciparum infected erythrocytes in the placenta, and the resulting inflammatory response affects maternal and child health. Despite existing information, little is known about the direct impact of P. falciparum on the placental barrier formed by trophoblast and villous stroma. This study aimed to assess placental tissue damage caused by P. falciparum in human placental explants (HPEs). Methods: HPEs from chorionic villi obtained of human term placentas (n = 9) from normal pregnancies were exposed to P. falciparum-infected erythrocytes (IE) for 24 h. HPEs were embedded in paraffin blocks and used to study tissue damage through histopathological and histochemical analysis and apoptosis using TUNEL staining. Culture supernatants were collected to measure cytokine and angiogenic factors and to determine LDH activity as a marker of cytotoxicity. A subset of archived human term placenta paraffin-embedded blocks from pregnant women with malaria were used to confirm ex vivo findings. Results: Plasmodium falciparum-IE significantly damages the trophoblast layer and the villous stroma of the chorionic villi. The increased LDH activity and pathological findings such as syncytial knots, fibrin deposits, infarction, trophoblast detachment, and collagen disorganization supported these findings. The specific damage to the trophoblast and the thickening of the subjacent basal lamina were more pronounced in the ex vivo infection. In contrast, apoptosis was higher in the in vivo infection. This disparity could be attributed to the duration of exposure to the infection, which significantly varied between individuals naturally exposed over time and the 24-h exposure in the ex vivo HPE model. Conclusion: Exposure to P. falciparum-IE induces a detachment of the syncytiotrophoblast, disorganization of the stroma villi, and an increase in apoptosis, alterations that may be associated with adverse results such as intrauterine growth restriction and low birth weight.